Markov processes and positive semigroups on some classes of weighted continuous function spaces - Altomare, Francesco; Musceo, Graziana (Rendiconti del Circolo matematico di Palermo, 2008)
In this paper we study strongly continuous positive semigroups on particular classes of weighted continuous function space on a locally compact Hausdorff space X having a countable base. In particular we characterize those positive semigroups which are the transition semigroups of suitable Markov processes. Some applications are also discussed. Keywords Positive semigroup, Markov transition function, Markov process, Weighted continuous function space, Degenerate second order differential operator Mathematics Subject Classification (2000) 47D06, 47D07, 60J60